Mapping acidic mine water using geophysics - De Villiers, Daniel Petrus de Wet (My University, 2018)
The oxidation of pyrite in water produces sulphuric acid that can decrease the pH of groundwater to the point where it is acidic itself. Furthermore, such an increase in acidity causes an increase in water conductivity. The water is referred to as acid mine drainage (AMD). It degrades the environment by enabling groundwater to carry high amounts of heavy metals. Efforts to remediate AMD effects in the Witwatersrand Basin include phytoremediation, specifically the use of Searsia lancea, Eucalyptus and Tamarix trees; these efforts are monitored by water periodically sampled from boreholes. This study investigates the potential of geophysical methods for identifying and monitoring the propagation of an AMD plume and the effects of phytoremediation associated with an old tailings dump in the Orkney area. The electrical resistivity method mapped the water table at a depth of 2-4 m and the maximum depth to bedrock at 18 m. Error analysis of the electrical resistivity data suggests that data can be interpreted down to a depth of only 10 m for profiles where the water is highly conductive due to its high level of contamination. The electrical resistivity results show a decrease in conductivity with distance from the contaminant source. In addition, a clear decrease in conductivity is observed downstream from a Tamarix woodland established for remediation. In the absence of metallic conductors in sediments the resistivity of the pore water governs the resistivity of the sediment medium. However, in this study the relationship determined between the conductivity of pore water and the geological unit is not linear and Archie's law is not applicable at this site, suggesting that either the resistivity of the surficial aquifer is poorly determined or the aquifer matrix is in itself conductive. The Induced Polarization (IP) method produces a chargeability response, which coincides with the Eucalyptus and Searsia lancea tree roots, suggesting that metallic contaminants are stored in and around the tree roots and are polarizable. Although ground penetrating radar has very little penetration in conductive media, GPR data were collected in an effort to image the plume geometry. However, the source waves did not penetrate through the topsoil due to the topsoil being conductive. This study demonstrates that the electrical resistivity method can effectively map the water table depth, can aid in groundwater conductivity mapping between boreholes and possibly tracking AMD. The data coverage of the electrical resistivity method was not sufficient to map the plume as a whole but does provide evidence for the effect of an established woodland in remediating groundwater. The IP method provides preliminary evidence for the removal of AMD pollutants from the groundwater by Searsia lancea and Eucalyptus tree roots.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science to the Faculty of Science, University of the Witwatersrand, Johannesburg, 2018
Keywords: Acid mine drainage; Pyrites